The Comparison of anxiety level between Taekwondo-Poomsae and Kyurogi players before competition - Callos, Aina Pearl R. 1995-; Maghanoy, Mona Liza A. (Quezon City College of Human Kinetics, University of the Philippines Diliman, 2019)
Taekwondo is the most popular Korean Martial Art and was recognized for the last 30 years as the first martial art to have an effective unarmed self-defense style. This study aims to evaluate the comparison of anxiety levels between Taekwondo-Poomsae and Kyurogi players before a competition. Anxiety is a state of uneasiness that can be accompanied by tension symptoms. As a result, situations that cause failure, misfortune and danger may be seen in individuals (Corman 2003). Anxiety consists of two parts cognitive and somatic anxiety. Cognitive anxiety is the mental part of concerns such as negative expectations or negative assessments of the person that may cause mental anxiety (Marten et al., 1999). While Somatic anxiety concerns the physiological and behavioral dimensions of anxiety that influence the person as a result of excitement and show sudden development (Martens et al., 1990). The self-confidence in individuals increases by the nature of this sport. For this reason, the virtues of manhood and humility incurred are based principally on a send of self-confidence (Gil 1978). Using the Competitive State Anxiety Inventory- 2 questionnaire to collect and measure the differences in terms of somatic anxiety, cognitive anxiety and self-confidence of both Taekwondo- Poomsae and Kyurogi players. It was found that there was a significant difference in Poomsae and Kyurogi players in terms of Cognitive Anxiety level. However, despite the finding, there was no significant difference in how they perceived the cognitive anxiety that was measured, whether it was facilitative or debilitative (p-value < 0.05). The difference in the level of Cognitive anxiety between Poomsae and Kyurogi was the only significant value found among all the measures. This study recommends a larger sample size and includes other variables such as years of experience, age, etc. to explore more relevant comparisons. Also, athletes in this study should look into psychological skills training to manage their anxieties.
Vita.
Thesis (Bachelor in Sports Science)--University of the Philippines Diliman
Keywords: Sports -- Psychological aspects; Performance anxiety; Anxiety -- Testing; Tae kwon do -- Philippines